Using Writing Process Approach (WPA) to Improve the Eight Grade Students' Ability in Mastering Writing Descriptive Text - Nora Fitria; Mela Monita (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
The aim of this study was to find out if there any significant differences between the students are taught descriptive text writing by using WPA and those without. This study used experimental research design. The population of this study was all eight grade students of SMP Negeri 1 Simeulue Barat, and the total population was 32 students. The sample of this study was the students of classes VIIIA and VIIIB. There were divided into two groups: the experimental and control groups. This study also used non random sampling. The data was collected from pre-test and post-test. The t-test analysis technique in this study used the SPSS 18 for windows. The mean of this study of post-test of the experimental group is 74.37, while the control group is 58.12. The writer obtained the results of in the t-count = 4.42, while t-table =2.05. So, the provisions in the different test if the t-count is higher than t-table then difference is real and the alternative hyhothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, in this study there was a significant difference in the achievement of writing descriptive text by using WPA. The use of WPA in teaching writing descriptive text is effective to be applied in the context at SMP Negeri 1 Simeulue Barat. Finally, the researchers suggest to teachers that students should use WPA in teaching descriptive text.